Computer Simulation Studies in Condensed-Matter Physics XIX - Landau, David P. (Springer, 2017)
This volume represents a "status report" emanating from presentations made during the 19th Annual Workshop on Computer Simulations Studies in Condensed Matter Physics at the Center for Simulational Physics at the University of Georgia in February, 2006. It provides a broad overview of the most recent advances in the field, spanning the range from equilibrium and non-equilibrium behavior in statistical physics to biological and soft condensed matter systems. Results on nanomagents and materials are included as are several descriptions of advances in methodology.